Neuroendocrine tumours of the female genital tract: a case-based imaging review with pathological correlation - Dias, João Lopes (2015)
Background Both primary and secondary gynaecological neuroendocrine (NE) tumours are uncommon, and the literature is scarce concerning their imaging features. Methods This article reviews the epidemiological, clinical and imaging features with pathological correlation of gynaecological NE tumours. Results The clinical features of gynaecological NE tumours are non-specific and depend on the organ of origin and on the extension and aggressiveness of the disease. The imaging approach to these tumours is similar to that for other histological types and the Revised International Federation of Gynecology and Obstetrics (FIGO) Staging System also applies to NE tumours. Neuroendocrine tumours were recently divided into two groups: poorly differentiated neuroendocrine carcinomas (NECs) and well-differentiated neuroendocrine tumours (NETs). NECs include small cell carcinoma and large cell neuroendocrine carcinoma, while NETs account for typical and atypical carcinoids. Cervical small cell carcinoma and ovarian carcinoid are the most common gynaecological NE tumours. The former typically behaves aggressively; the latter usually behaves in a benign fashion and tends to be confined to the organ. Conclusion While dealing with ovarian carcinoids, extraovarian extension, bilaterality and multinodularity raise the suspicion of metastatic disease. NE tumours of the endometrium and other gynaecological locations are very rare. Teaching Points • Primary or secondary neurondocrine (NE) tumours of the female genital tract are rare. • Cervical small cell carcinoma and ovarian carcinoids are the most common gynaecological NE tumours. • Cervical small cell carcinomas usually behave aggressively. • Ovarian carcinoids tend to behave in a benign fashion. • The imaging approach to gynaecological NE tumours and other histological types is similar.